Biocatalytic stereoselective synthesis of pyrrolidine-2, 3-diones containing all-carbon quaternary stereocenters. Issue 13 (14th March 2023) - Shahedi, Mansour; Omidi, Niloofar; Habibi, Zohreh; Yousefi, Maryam; Brask, Jesper; Notash, Behrouz; Mohammadi, Mehdi
Abstract : The diastereoselective synthesis of all-carbon benzylic quaternary stereocenters via conjugate addition of pyrrolidinones to ortho -quinones catalyzed by laccase under mild reaction conditions is reported. Abstract : Highly functionalized pyrrolidine-2, 3-diones can be synthesized efficiently and stereoselectively under mild conditions using a biocatalytic approach. The reaction led to the formation of new all-carbon quaternary stereocenters from Myceliophthora thermophila laccase (Novozym 51003) catalyzed oxidation of catechols to ortho -quinones and subsequent 1, 4-addition with 3-hydroxy-1, 5-dihydro-2 H -pyrrol-2-ones. The reaction was conducted with various substituents on both reactants, resulting in 13 products in moderate to good yields (42–91%). The same 15 reactions were also tested with K3 Fe(CN)6 as a catalyst, but here only one reaction resulted in a product (60% yield).